Agricultural development and the conservation of avian biodiversity on the Eurasian steppes: a comparison of land‐sparing and land‐sharing approaches. Issue 6 (23rd September 2015) - Kamp, Johannes; Urazaliev, Ruslan; Balmford, Andrew; Donald, Paul F.; Green, Rhys E.; Lamb, Anthony J.; Phalan, Ben
Summary: The break‐up of the Soviet Union in 1991 led to the abandonment of >40 million ha of cropland, a collapse in livestock numbers and the recovery of depleted biodiversity on the steppe grasslands of Kazakhstan and southern Russia. More recently, large‐scale reclamation of abandoned cropland and intensification of agriculture are observed, highlighting a need for strategies to reconcile agricultural development and biodiversity. We related bird densities along a land‐use gradient to yield estimates from arable and livestock systems in central Kazakhstan to decide whether a land‐sparing, a land‐sharing or an intermediate strategy would result in the largest benefits for biodiversity. For 'loser species' (whose population size is reduced by farming), land sparing was predicted to support higher total populations of more species than was land sharing, at all production targets. 'Winners' (species benefitting from agriculture) profited from land sharing when judged from food energy or protein. Intermediate yields were best for very few species. Heavily grazed steppe grassland was important for several globally threatened and biome‐restricted species. Government statistics suggested that over 50% of abandoned cropland has been reclaimed since 2000 and crop yields have increased. In the same period, there was significant progress towards the designation of new protected areas, but the total area in Kazakhstan still falls short of the Convention on Biological Diversity's 17% target. Policy implications . Further increases in agricultural production are likely to reduce populations of most birds, especially if they are achieved by conversion of abandoned cropland, or grassland. Our results suggest that production increases would do least harm if they resulted from increasing the output of existing cropland, using approaches such as snow accumulation, no‐till and more efficient grain harvesting and storage, rather than from further reclamation of abandoned land that is now reverting back to steppe. Production increases should be offset by improved conservation planning through the designation of protected areas on land potentially suitable for cropland expansion.